Supply Chain Agility Evaluation Using Fishbone Method - Rahman, Dewi Sofiah (The International Journal of Business Review (The Jobs Review), 2021)
The publishing industry is considered as an industry that has a low entry barrier. Supply chain agility refers to the level of speed that the supply chain uses to respond to customer needs. Supply chain agility represents the ability of an organization's internal supply chain functions to provide strategic advantages and innovations to respond to market uncertainty. Supply chain agility is also considered as a key element of an organization's competitive strategyÂ  which requires an evaluation method. Fishbone Diagrams or Cause and Effect Diagrams are one of the tools of QC 7 tools that are used to identify and show the relationship between cause and effect in order to find the root causes of a problem. This study used "Supply Chain Agility" as an effect factor, and cause factors derived from The 4 M's theory and 4 Indicators of supply chain agility theory. The result of study are several factors indicate the weaknesses of the company that must be evaluated and several factors indicate the strengths that must be maintained